Welcome to murder week - Dukess, Karen (Gallery/Scout Press, 2025)
"A funny, heartfelt, delightful novel about an American woman who, following the death of her absentee mother, finds tickets her mother had inexplicably purchased for them to take part in a murder mystery simulation in a small English town and decides to go on the trip"--